2012
DOI: 10.1080/13607863.2012.678478
|View full text |Cite
|
Sign up to set email alerts
|

Depression, hippocampal volume changes, and cognitive decline in a clinical sample of older depressed outpatients and non-depressed controls

Abstract: Objective The aim of this study was to develop and test a model of depression, hippocampal changes, and cognitive decline. Method Participants were 248 community-dwelling, depressed patients and 147 healthy, non-depressed individuals 60 years and older. Participants received a structured interview assessing current depressive symptoms and past depressive episodes, completed cognitive testing with the MMSE, and underwent structural MRI of the brain. For up to ten years, assessment of depressive symptoms and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 42 publications
1
57
1
1
Order By: Relevance
“…Meta-analyses from numerous MRI studies have since confirmed this observation (Videbech and Ravnkilde 2004;Geuze et al 2005;McKinnon et al 2009). This same correlation holds true even for late-onset depression (Sawyer et al 2012;Sexton et al 2012). Postmortem observations have also confirmed similar reductions in hippocampal volume (Rajkowska et al 1999), but it is not yet known whether a decrease in adult neurogenesis is a contributing factor and to what extent.…”
Section: Depressionsupporting
confidence: 54%
“…Meta-analyses from numerous MRI studies have since confirmed this observation (Videbech and Ravnkilde 2004;Geuze et al 2005;McKinnon et al 2009). This same correlation holds true even for late-onset depression (Sawyer et al 2012;Sexton et al 2012). Postmortem observations have also confirmed similar reductions in hippocampal volume (Rajkowska et al 1999), but it is not yet known whether a decrease in adult neurogenesis is a contributing factor and to what extent.…”
Section: Depressionsupporting
confidence: 54%
“…A meta-analysis showed that patients with depression had a smaller hippocampal volume than healthy people (Videbech and Ravnkilde, 2004). A decrease in hippocampal volume predicted lower scores in cognitive tests over a four-year period (Sawyer et al, 2012). Long-term depressive symptoms may further decrease the volume of hippocampus and increase the risk of developing cognitive decline.…”
Section: Longitudinal Association Of Depressive Symptoms With Cognitimentioning
confidence: 98%
“…For instance, post-mortem studies and imaging techniques such as MRI have shown an associated hippocampal atrophy or loss in hippocampal volume in depressed patients (MacQueen et al, 2008; Maller et al, 2007; Malykhin et al, 2010; Neumeister et al, 2005; Sawyer et al, 2012). In one human study of depression, use of selective serotonin reuptake inhibitors (SSRIs) and tricyclic and tetracyclic antidepressants (TCAs) was correlated with an increase in overall dentate gyrus volume and also increased neural progenitor cells in the anterior hippocampus (Boldrini et al, 2009).…”
Section: Adult Hippocampal Neurogenesis: Understanding Preclinicalmentioning
confidence: 99%